Enhancing Good Governance in South Africa Through Youth Protest : A Catalyst for Social Change - Andrew Enaifoghe; Durokifa Anuoluwapo Abosede (Researchers World - International Refereed Social Sciences Journal, 2021)
Purpose: This study looked at youth protest as a catalyst for social change in enhancing good governance in South Africa. The aftermath of apartheid presented South Africa scouring for good governance. The successive governments constantly restructured social and economic sectors through policy implementation and ambitious programs to promote good governance. Yet, there has been numerous demonstrations and protests reminiscing the days of the anti-apartheid struggle, particularly towards the quality of service delivery provided. Methodology: The paper is a qualitative study, which employed eclectic literature in analysing the role of youth protest towards the promotion of good governance in South Africa. Findings: The study discussed the reason for the occurrence of youth protest in South Africa, as well as how it could promote good governance is strategically managed. Implication: The study emphasizes the catalytic role protests play as social change in enhancing good governance. Originality: So far, no available study has identified youth protest as a catalyst for social change in enhancing good governance in South Africa. Conclusion: It was recommended that government should include and involve more youths in integral processes like constitutionalism, rule of law and leadership roles.